The Impact of the Role of Electronic Accounting on the Quality of Financial Reports in Banks: (Study the Case of Banks Operating in the Cities of Kosti and Rabak) - منى حسين محمد أحمد; خضر الطيب الأمين (White Nile Journal for Studies and Research, 2022)
The study aimed to investigate the role of electronic accounting systems in achieving the quality of financial reports (case study of banks operating in the cities of Kosti and Rabek 2021), by studying the impact of the electronic operation of the accounting system on the output of financial reports. Financial reports?, Based on the study problem and its objectives, the following hypotheses were tested: There is a statistically significant relationship between the method of operating the accounting system and the quality of financial reports, there is a statistically significant relationship between the computerization of the accounting system and the quality of financial reports. The electronic accounting system helps to raise the efficiency of the quality of financial reports. Electronic accounting contributes to providing information with high credibility. One of the recommendations of the study is to give the elements of electronic operation of the accounting system greater confidence to raise the efficiency and quality of financial reports in banks